Persepsi Konsumen Muslim terhadap Kaidah Al-Yaqin La Yazulu Bisy-syakk dalam Transaksi E-Commerce Syariah - Nabila Mutia Syifa; Dinda Alya Nazwa. S; Yoga Prawira Rukmana; Abdul Rahman Sofyan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
The rapid growth of Sharia-based e-commerce reflects the increasing demand among Muslim consumers for transactions that comply with Islamic principles. However, digital transaction practices still raise various concerns, particularly regarding the clarity of contracts (akad), payment security, and information transparency. This study aims to explain Muslim consumers’ perceptions of the application of the legal maxim al-yaqīn lā yazūlu bi al-shakk in Sharia e-commerce transactions, with a focus on students of the State Islamic University of North Sumatra. This research employs a descriptive qualitative approach, using in-depth interviews with 10 informants as the primary data source, supported by questionnaire data to identify general tendencies in respondents’ perceptions. The findings reveal that although most respondents understand the maxim theoretically, they have not been able to apply it effectively in digital transaction contexts. The uncertainties experienced by respondents are predominantly triggered by technical factors, such as delays in payment confirmation, rather than shakk in the fiqh sense. Moreover, limited understanding of digital contract mechanisms contributes to uncertainty regarding the moment when a contract is considered legally valid. Information transparency emerges as a key factor in fostering yaqīn, particularly in relation to the clarity of product descriptions and transaction procedures. This study concludes that the application of al-yaqīn lā yazūlu bi al-shakk in Sharia e-commerce remains suboptimal due to limited digital fiqh literacy and insufficient technological reliability, highlighting the need for enhanced digital muamalah education and improved information quality on Sharia e-commerce platform.